2008
DOI: 10.1016/j.seizure.2007.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Should we reconsider epilepsy surgery? The motivation of patients once rejected

Abstract: The pre-surgical work-up of patients with medically refractory epilepsy changes with the availability of new diagnostic procedures. New diagnostic investigations may also open up prospects for patients rejected in the past. A cohort of 71 Dutch patients rejected for epilepsy surgery 0.5-5 years earlier were approached to evaluate their willingness to undergo novel techniques. 64 (90%) responded to a questionnaire evaluating social and medical status, quality of life (QoL) and motivation to be reconsidered for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The obvious potential use of scalp EEG-fMRI is as a noninvasive tool to help localize epileptic activity as part of the pre-surgical evaluation of patients with focal epilepsy [30,31]. The accurate spatial localization of epileptiform EEG activity remains central in both the diagnosis and treatment of epilepsy.…”
Section: Epilepsy: Localization Of Epileptogenic Generatorsmentioning
confidence: 99%
“…The obvious potential use of scalp EEG-fMRI is as a noninvasive tool to help localize epileptic activity as part of the pre-surgical evaluation of patients with focal epilepsy [30,31]. The accurate spatial localization of epileptiform EEG activity remains central in both the diagnosis and treatment of epilepsy.…”
Section: Epilepsy: Localization Of Epileptogenic Generatorsmentioning
confidence: 99%
“…Vagus nerve stimulator (VNS) implantation is a viable treatment option for those who are not surgical candidates . Little is known about the group of patients who had been rejected from epilepsy surgery, and there are few reports describing their long‐term outcome . Most of the patients described as being rejected from surgery in the above‐cited studies had been evaluated more than a decade ago: ~5–20% of them reported that they had become seizure‐free, and up to 76% reported a reduction in seizure frequency over time .…”
Section: Introductionmentioning
confidence: 99%
“…115 The potential clinical value lies in its ability to corroborate negative evidence regarding surgical candidacy, suggesting poor postsurgical outcome, or to suggest reconsideration of surgery after previous rejection as surgical candidates. [116][117][118] Scalp EEG-fMRI can also map seizure-related BOLD networks during and before seizures. Seizures were captured either by chance during interictal studies [119][120][121][122][123] or intentionally.…”
Section: Simultaneous Electroencephalographyfunctional Magnetic Resonmentioning
confidence: 99%